Performace of wind turbine based on wind speed data and turbine tower height in Kangar, Northern Malaysia - Ismail, Daut, Prof. Dr.; Muhammad Irwanto, Misrun; Mohd Irwan, Yusoff; Gomesh Nair, Shasidharan; Noor Syafawati, Ahmad (Australian Journal of Basic and Applied Sciences, 2012)
Link to publisher's homepage at http://www.insipub.com/